Social Identity Complexity, Corporate Social Responsibility, and Brand Love of Multiple Leagues in Professional Sport - Do, Chanwook; Brison, Natasha T.; Park, Juho; Lee, Hyun-Woo (Frontiers in Psychology, 2022)
How can corporate social responsibility initiatives influence brand love? Based on the theory of social identity complexity, we examined whether greater complexity of a sport fan’s multiple identifications with sport leagues led to higher multicultural tolerance and more positive perceptions of leagues’ corporate social responsibility activities. Further, brand authenticity was tested as a variable intervening between perceived corporate social responsibility and brand love. We analyzed this serial mediation effect impacting sport fans’ brand love for their multiple, favored and less favored, sport leagues. Participants (N = 242 Amazon Mechanical Turk workers) answered the scale item questionnaire for model assessment. The hypothesized model was supported as the indirect effect through all mediators was significant (43.42% of total indirect effects). Our results suggest that when sport fans acknowledge a high overlap among league fan groups (low social identity complexity), their tolerance is more likely to be higher than those who have a low overlap. Such high levels of tolerance influence how fans perceive corporate social responsibility initiatives, and these effects build up for fans to perceive the brand to be more authentic (i.e., based on their continuity, credibility, integrity, and symbolism). These antecedents affected brand love through a serial mediation. Sport league managers should consider the diverse aspects across leagues (i.e., different fan characteristics, media operations, game schedules) for harmonious coexistence with other leagues (e.g., by collaborating on promotions and reducing overlap of schedules) and maintain brand authenticity for their social initiatives to result in a greater brand love in the consumer’s mind.